Gender Inequality of Pregnant Women in the Workplace: A Legal Framework Perspective on Pregnancy Rights - Putri Rahmah Nur Hakim; Irwan Abdullah; Annisa Dwi Lestari; Cut Irna Liyana; Aklima Aklima; M. Nastain (Universitas Gadjah Mada, 2026)
The phenomenon of job termination (PHK) and promotion failure for pregnant women is a crucial issue reflecting gender inequality in the workplace. Although various studies have addressed gender-based discrimination, research that specifically examines the psychosocial impact of job termination and promotion failure on pregnant women remains limited. This study aims to understand the subjective experiences of pregnant women affected by job termination or promotion failure and to analyze how these conditions influence their emotional and social wellbeing. This research employs a qualitative approach using in-depth interviews with several pregnant women who experienced job termination or promotion failure. Secondary data is collected through a systematic analysis of relevant online news articles. The data analysis process for this study uses thematic analysis to identify patterns of experience and the main contributing factors. The main findings reveal that job termination and promotion failure lead to high emotional distress, financial anxiety, and a sense of lost professional identity. This study contributes conceptually to understanding gender-based discrimination and enriches qualitative research methods through the combination of primary and secondary data. The study’s limitations include a limited number of Informant and the potential bias of secondary data sources. Future research is recommended to expand the number and diversity of Informant, adopt a longitudinal approach, and advocate for gender-based labor protection policies to create a more inclusive and equitable work environment